2017
DOI: 10.21873/anticanres.11895
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Levels of VEGF and CXCL1 Are Predictive of Metastatic Organotropismin in Patients with Colorectal Cancer

Abstract: Colorectal cancer is the most common cancer of the gastrointestinal system and has a marked preference to metastasize to distant organs. In this study, we investigated whether levels of circulating serum pro-angiogenic cytokine such as chemokine (C-X-C motif) ligand 1 (melanoma growth-stimulating activity, alpha; CXCL1) and vascular endothelial growth factor (VEGF) have a role in favoring the colonization of metastatic cells at preferential sites and determined their prognostic significance in a cohort of 103 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 31 publications
1
25
1
Order By: Relevance
“…CXCL1 is upregulated in various cancers and associated with cancer progression, such as cancer cell growth, proliferation, tumor angiogenesis and metastasis, after the activation of CXCR2 [27,28,29]. In addition, CXCL1 is not only involved in cancer progression, but also responsible for resistance to several chemotherapeutic drugs, such as oxaliplatin, doxorubicin, and cyclophosphamide [30,31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…CXCL1 is upregulated in various cancers and associated with cancer progression, such as cancer cell growth, proliferation, tumor angiogenesis and metastasis, after the activation of CXCR2 [27,28,29]. In addition, CXCL1 is not only involved in cancer progression, but also responsible for resistance to several chemotherapeutic drugs, such as oxaliplatin, doxorubicin, and cyclophosphamide [30,31,32,33].…”
Section: Discussionmentioning
confidence: 99%
“…Chemokine (C-X-C motif) ligand 1 (CXCL1), also named GRO-α, is a member of the G protein-coupled receptor family that binds specifically to CXC chemokine receptor 2 [ 11 , 12 ]. CXCL1 is overexpressed in CRC and facilitates metastasis and progression [ 13–15 ]. However, the prognostic significance of CXCL1 overexpression and related underlying mechanisms are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in a study conducted on seventy CRC patients, it was found that serum VEGF expression levels, determined by ELISA, were significantly correlated with advanced stage and metastases but not with age, gender, and tumor localization [ 14 ]. Another study, involving a cohort of one-hundred three CRC patients, reported that elevated circulating levels of VEGF were prognostic for liver and lung metastasis [ 104 ]. Kwon and colleagues have examined the expression levels of VEGF, IL-6 and C-Reactive Protein in patients who underwent curative resection for CRC and determined their reciprocal association and with histological findings.…”
Section: Angiogenesis-related Prognostic Biomarkers In Crcmentioning
confidence: 99%
“…Also, gene polymorphism in VEGF-A could hold prognostic information: a recent study demonstrated that the homozygous genotype VEGF-2578 AA had significant effect on time to tumor recurrence [ 106 ]. In order to strengthen the prognostic value of VEGF, some studies have suggested the parallel evaluation for circulating cytokines, including the chemokine, CXC motif, Ligand 1 (CXCL1), and IL-6 [ 104 ]. However, results from these studies were contradictory [ 105 ].…”
Section: Angiogenesis-related Prognostic Biomarkers In Crcmentioning
confidence: 99%